EKSISTENSI KOMISI KEJAKSAAN REPUBLIK INDONESIA DALAM RANGKA MEWUJUDKAN PENEGAKAN HUKUM YANG BAIK DI INDONESIA - Sultan Fadillah Effendi; Dodi Haryono; Zainul Akmal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
In the Indonesian constitutional system, the Prosecutor's Office of the Republic ofIndonesia is one of the institutions that contribute to law enforcement. To improve the qualityand capability of prosecutors and prosecutorial employees, it is necessary to have aninstitution that supervises, monitors, and assesses the performance of prosecutors andprosecutors in carrying out their obligations, as stated in Article 38 of the Law on theProsecutor's Office of the Republic of Indonesia. On the basis of this, the Attorney General'sCommission of the Republic of Indonesia was formed as an additional institution thatspecifically carries out this function. The research objectives of this thesis are first, toanalyze the existence of the Prosecutor's Commission as a state auxiliary agency based onapplicable laws and regulations. Second, to analyze the ideal arrangement of theProsecutor's Commission as a state auxiliary agency in order to realize good lawenforcement in the future.This type of research can be classified into normative legal research with thetype of legal systematics and legal principles. This research uses data sources in the form ofsecondary data with literature study-based data collection techniques.From the results of the problem research there are two main things that canbe concluded. First, the existence of the Prosecutor's Commission as State Auxiliary Agenciesbased on applicable laws and regulations, namely as an additional state institution that isnon-structural independent and is in the executive realm. Institutionally, the Prosecutor'sCommission is relatively weak starting from the position, legal basis, duties and authoritiesand financial rights that are not yet independent. Second, the ideal arrangement for theProsecutor's Commission as a state auxikiary agency in order to realize good lawenforcement in the future is to clarify the position of the Prosecutor's Commission as anindependent institution, increase the legal basis at the level of the Law, simplify the task andauthority procedures and the independent financial rights of the Prosecutor's Commission.The author's suggestions are First, the legislator should revise Article 38 of the Prosecutor'sOffice Law and strengthen the position of the Prosecutor's Office Commission as anindependent institution with a regulation at the level of law. Second, it is recommended thatthere be an expansion of the authority of the Prosecutor's Commission in the form ofexecutorial power. Third, the addition of authority for monitoring within a certain period oftime. Fourth, there is authority over financial rights by the Prosecutor's Commissionindependently. Thus it will strengthen the existence of the Prosecutor's Commission inrealizing good law enforcement in the future.Keywords: Existence, Prosecutorial Commission and Law Enforcement.